When the fail open valve fails closed: Lessons from investigating the "impossible". Issue 3 (13th December 2018) - Dee, Sean J.; Cox, Brenton L.; Ogle, Russell A.
Abstract : Process hazard analysis is recognized by many safety professionals and regulatory groups as the key provision of a process safety management system. This analysis evaluates what can go wrong, and what safeguards are needed to prevent incidents. One challenge in process hazard analysis is the reliance on humans to determine reasonable, expected, or anticipated failure modes. The implementation of safeguards may also foster a lost sense of vulnerability to potential process upsets. These factors in combination can lead to a disregard for failure modes considered "unlikely" or even "impossible." Unfortunately, this problem is often revealed when the "impossible" leads to an incident or accident. In this article, a case study is used to motivate a discussion of incidents involving hazards that were disregarded in process hazard analysis due to their low probability, or supposed impossibility. Tools, techniques, and guidance will be discussed to improve process hazard analysis when evaluating low probability failure modes. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: e12031, 2019